The homotopy theory of commutative dg-algebras II - Oberdieck, Georg (Eidgenössische Technische Hochschule Zürich (ETH Zürich), 2013)
Cotangent complexes, derivations and obstruction theory. Application to mapping spaces of commutative dg-algebras
Audiovisuelles Material